2001
DOI: 10.1097/00042728-200107000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Photorejuvenation for Asian Skin by Intense Pulsed Light

Abstract: background. Dermabrasion and deep chemical peeling are used in the treatment of photoaged skin. These ablative procedures are effective enough to produce a certain improvement but have often caused postinflammatory hyperpigmentation among Asian patients. To avoid such adverse effects, a new, nonablative procedure has been sought. objective. To determine the effectiveness of photorejuvenation for Asian skin using intense pulsed light (IPL). The specific parameters used, improvement ratios, side-effects, and dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 14 publications
(15 reference statements)
0
26
0
Order By: Relevance
“…IPL is widely used and has beneficial effects on photoaged skin in Asians, especially on pigmented lesions, but wrinkles and elasticity are minimally affected. [5][6][7] Previous research demonstrated that these nonablative modalities failed to show any significant improvements on rhytides, and 68% of patients reported uncertain or no efficacy on rhytides. Although no published study has directly shown that RF and IPL combined is superior to IPL alone, with IPL combined with a bipolar RF device, a greater degree of wrinkle reduction was revealed than observed with pulsed light treatments alone.…”
Section: Discussionmentioning
confidence: 99%
“…IPL is widely used and has beneficial effects on photoaged skin in Asians, especially on pigmented lesions, but wrinkles and elasticity are minimally affected. [5][6][7] Previous research demonstrated that these nonablative modalities failed to show any significant improvements on rhytides, and 68% of patients reported uncertain or no efficacy on rhytides. Although no published study has directly shown that RF and IPL combined is superior to IPL alone, with IPL combined with a bipolar RF device, a greater degree of wrinkle reduction was revealed than observed with pulsed light treatments alone.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, the Q-switched alexandrite laser with a wavelength of 755 nm was reported to be highly effective for removing freckles. 10 Recently, the effectiveness of the combined use of QSRL and intense pulsed light (IPL) as another light source [11][12][13] for the treatment of complex dyspigmentation has been described. 14 In most in vivo studies, a histological approach to examine changes after laser therapy has not been possible because of the limitation of performing a biopsy during the recovery process.…”
mentioning
confidence: 99%
“…Only 3 patients had blisters. 8 However, traditional IPL sources have the ''V-shaped'' energy peak of pulses that could increase the risk of skin burning and postinflammatory hyperpigmentation (PIH). Thus, a novel IPL source (Lumenis One, Lumenis Co., Santa Clara, CA) incorporating optimal pulse technology was developed.…”
mentioning
confidence: 99%